Impact of SGLT2 inhibitor on mortality and cardiovascular outcomes in patients with type 2 diabetes mellitus with left main or multivessel coronary artery disease. (3rd October 2022) - Chipayo Gonzales, D A; Salinas, P; Fuentes, M; Vergara, C; Espejo-Paeres, C; McInerney, A; Tirado-Conte, G; Macaya-Ten, F; Mejia-Renteria, H; Nunez-Gil, I; Gonzalo, N; Jimenez-Quevedo, P; et al.
Abstract: Background: Sodium-glucose Cotransporter 2 inhibitors (SGLT2-i) have shown improved cardiovascular outcomes in type 2 diabetes mellitus (T2DM) that surpass their hypoglycaemic power. However, the inclusion criteria in the pivotal studies were broad in terms of cardiovascular disease, and there are no specific studies on patients with coronary artery disease (CAD). Purpose: To compare, in patients with T2DM and extensive CAD, the hazard ratio (HR) of all-cause death in patients treated with or without SLGT2-I, adjusted by IPTW and treatment (revascularization) strategy. Secondary: To compare the adjusted HR of cardiovascular (CV) death, myocardial infarction (MI), stroke, or heart failure admission (HF) in patients treated with or without SLGT-I. Methods: A single-centre retrospective observational study in patients with T2DM, with the first diagnosis of extensive CAD defined by >50% stenosis in LM or 3-vessels, and alive at discharge. The study was approved by the research ethics committee and recruited consecutive patients from 2015 (year of first SLGT2-I approval) to 2020. Patients with prior revascularization, severe renal failure (filtration rate <30 ml/min), less than 6 months of SLGT2-I treatment and less than 1 year of follow-up were excluded. Results: We recruited 420 patients with a mean age of 71.2±11.1 years; 78.6% were male, 82.6% had hypertension, 72% hyperlipemia, 50.2% were smokers or former smokers, 52.9% had a history of previous myocardial infarction and 10.7% of stroke. Mean LVEF (%) was 51.5±1.5, creatinine clearance 73.94±22 ml/min and glycated haemoglobin (%) 7.3±1.2. The presentation was acute coronary syndrome in 44.3% (27% ST elevation/73% non-ST elevation). LM was affected in 29%; 3-vessel CAD was found in 86.7%; 2-vessel in 8.3%; 1-vessel in 3.8%, and 1.2% exclusively in the LM. Treatment strategy was PCI + OMT in 48.3%, CABG + OMT 39.8% and OMT only in 21.9%. T2DM treatment, secondary prevention treatment and metabolic control at follow up are presented in Table 1. A total of 104 patients (24.8%) started treatment with SGLT2-I during a mean of 1.6±1 years. At a mean follow-up of 3±1.6 years, mortality was 16.4%, CV mortality was 9.5%, 6.9% had a MI, 3.3% had a stroke, and 11.4% had HF admission. Patients treated with SLGT2-I had a lower risk of all-cause death, cardiovascular death and the composite of CV death or HF (Table 2). After IPTW, the risk of all-cause death was persistently lower in the SLGT-I group Conclusion: This real-life study found that in T2DM patients with LM or MVD only 1 out of 4 patients was treated with SGLT2-I as a part of their secondary prevention treatment. Those with SGLT2-I had a reduced risk of all-cause death (HR 0.34 [0.12–0.91], p=0, 033) after IPTW and treatment (revascularization) strategy adjustment. Funding Acknowledgement: Type of funding sources: None.